Morphometric analysis and growth patterns of the mudskipper (Periophthalmus chrysospilos) in the Kuala Mangrove Area of Kota Langsa - Diyah Anjani; Sakina Azzahra Hilal; Intan Baiduri; Adelia Putri; Selvira Selvira; Abdul L. Mawardi (Acta Aquatica: Aquatic Sciences Journal, 2026)
The Kuala Mangrove area in Kota Langsa has high biodiversity potential and plays an important role as a habitat for the mudskipper (Periophthalmus chrysospilos). However, information regarding the morphometric characteristics and growth patterns of this species in the area remains limited. This study aimed to analyze the morphometric characteristics and growth patterns of mudskippers in the Kuala Mangrove area of Kota Langsa. The research was conducted in October 2025 using a survey method with a purposive sampling technique. Observed parameters included fish body morphometric measurements and environmental factors such as temperature, pH, and salinity. Data were processed using Microsoft Excel to obtain average values and length–weight relationships through logarithmic regression analysis. The results showed that 44 mudskipper individuals were found at three observation stations, with average total lengths of 18.2 ± 1.8 cm (Station 1), 20.9 ± 1.3 cm (Station 2), and 23.9 ± 1.8 cm (Station 3), and corresponding body weights of 109.8 ± 14.6 g, 137.4 ± 13.7 g, and 179.4 ± 16.5 g. The b values at each station were 1.39, 1.69, and 1.21, with determination coefficients (R²) of 0.99, 0.99, and 0.96, indicating a negative allometric growth pattern. Environmental conditions such as temperature 28–30°C, pH 7.2–7.6, and salinity 25–30 ppt were within the optimal range. These findings indicate that mudskippers possess a high adaptive capacity and have potential as bioindicators of the mangrove ecosystem in the Kuala Mangrove area of Kota Langsa. Keywords: Growth Pattern; Mangrove; Morphometric; Mudskipper; Periophthalmus chrysospilos